Stingless bee (Heterotrigona itama) honey and its phenolic-rich extract ameliorate oxidant–antioxidant balance via KEAP1-NRF2 signalling pathway - Zulhilmi Cheng, Mohamad Zulhafiz Shafiq; Zulkhairi Amin, Fatin Aina; Zawawi, Norhasnida; Chan, Kim Wei; Ismail, Norsharina; Ishak, Nur Akmal; Mohd Esa, Norhaizan (Multidisciplinary Digital Publishing Institute, 2023)
Diabetes is associated with an imbalance between oxidants and antioxidants, leading to oxidative stress. This imbalance contributes to the development and progression of diabetic complications. Similarly, renal and liver diseases are characterised by oxidative stress, where an excess of oxidants overwhelms the antioxidant defense mechanisms, causing tissue damage and dysfunction. Restoring the oxidant–antioxidant balance is essential for mitigating oxidative stress-related damage under these conditions. In this current study, the efficacy of stingless bee honey (SBH) and its phenolic-rich extract (PRE) in controlling the oxidant–antioxidant balance in high-fat diet- and streptozotocin/nicotinamide-induced diabetic rats was investigated. The administration of SBH and PRE improved systemic antioxidant defense and oxidative stress-related measures without compromising liver and renal functioning. Analyses of the liver, skeletal muscle and adipose tissues revealed differences in their capacities to scavenge free radicals and halt lipid peroxidation. Transcriptional alterations hypothesised tissue-specific control of KEAP1-NRF2 signalling by upregulation of Nrf2, Ho1 and Sod1 in a tissue-specific manner. In addition, hepatic translational studies demonstrated the stimulation of downstream antioxidant-related protein with upregulated expression of SOD-1 and HOD-1 protein. Overall, the results indicated that PRE and SBH can be exploited to restore the oxidant–antioxidant imbalance generated by diabetes via regulating the KEAP1-NRF2 signalling pathway.